IMPLEMENTASI KEBIJAKAN INDONESIA DALAM MENANGANI IMIGRAN ILEGAL (STUDI KASUS : PROVINSI RIAU) - Nofyora Rahayu; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explains the implementation of Indonesian policy in handling illegal immigrants in Riau province. Riau which is located very strategically and located on the border of the sea with other countries allows so many people who visit Riau for a tour as well as for asylum seekers. Due to the factors that make the asylum seekers make Riau as their place to go to their destination country that is AustraliaThe perspective used in this research is neorealism, the theory used is migration and policy. The data used in this study are primary and secondary data. Primary data obtained from field research and data collection were conducted using interviews based on structured questions. Secondary data is obtained through library research, and online computer search. The data obtained are then selected and then analyzed in a qualitative manner and prepared in the form of descriptive research reports.The study finds that now Indonesia can only accept the refugees until the third State for the refugees already exists. Increasingly, more and more foreign nationals are victims of conflict in their country who come to Indonesia. Because according to them Indonesia is a very good country. That way, Indonesia must continue to receive refugees because it is a mandate of the United Nations and Indonesia should keep. Coordination of fereign parties, Namely UNHCR and IOM determine and influence. In determining the status and facilities for asylum seeker and refugees.Keywords: Illegal Immigrants, Indonesian Policy